Dissecting saving dynamics: Measuring wealth, precautionary, and credit effects - Christopher D. Carroll; Jiri Slacalek; Martin Sommer (Goethe University Frankfurt, Center for Financial Studies (CFS), 2012)
We argue that the US personal saving rate's long stability (1960s-1980s), subsequent steady decline (1980s-2007), and recent substantial rise (2008-2011) can be interpreted using a parsimonious buffer stock model of consumption in the presence of labor income uncertainty and credit constraints. Saving in the model is affected by the gap between target and actual wealth, with the target determined by credit conditions and uncertainty. An estimated structural version of the model suggests that increased credit availability accounts for most of the long-term saving decline, while fluctuations in wealth and uncertainty capture the bulk of the business-cycle variation.
urn:nbn:de:hebis:30:3-272536
Keywords: E21; E32; 330; Consumption; Saving; Wealth; Credit; Uncertainty; Sparen; Gesamtwirtschaftlicher Konsum; Buffer-Stock-Ansatz; Lohn; Risiko; Verschuldungsrestriktion; USA